The Weather Privateers: Meteorology and Commercial Satellite Data. - Cirac-Claveras, Gemma (Information & Culture, 2018)
This article examines the changing framework for producing satellite weather data in the United States since the 2000s, from a government function to one increasingly carried out by the private sector. It explores the controversial attempts to commercialize the production of a particular data source (atmospheric profiles obtained with radio occultation) from the perspective of executives of the National Oceanic and Atmospheric Administration (NOAA), members of Congress, atmospheric and climate scientists, and the private sector. It addresses their opposing arguments by focusing, in particular, on the stresses and pressures within NOAA and its resistance to acquiring such data from commercial providers. In so doing, the article discusses the connections between commercial activities and meteorology and, more generally, the relations between science and commerce.